2016
DOI: 10.1039/c6ra17269e
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of an efficient one-pot synthesis of 6H-pyrrolo[2,3,4-gh]perimidines in polyphosphoric acid

Abstract: Several highly efficient one-pot synthetic protocols were developed, enabling polyphosphoric acid-activated nitroalkanes to act as electrophiles in reactions with aminonapthalenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…It was also discovered that the nucleophilic amines 3 can be successfully employed in this type of transformations as well, providing the amidinium intermediates 4 , which are susceptible to a variety of subsequent cyclizations. This approach opens up a novel avenue by which to access the benzoxazoles 5 [ 40 ], benzimidazoles 6 [ 40 41 ], diazines 7 [ 42 43 ], or imidazolines 8 ( Scheme 1 ) [ 44 ]. We have also shown that a nucleophilic attack on the phosphorylated nitronate species 2 can be carried out with the participation of N -acylhydrazides or thiosemicarbazides to afford the 1,3,4-oxadiazoles 9 [ 45 ] and the 1,3,4-thiadiazoles 10 [ 46 ], respectively ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was also discovered that the nucleophilic amines 3 can be successfully employed in this type of transformations as well, providing the amidinium intermediates 4 , which are susceptible to a variety of subsequent cyclizations. This approach opens up a novel avenue by which to access the benzoxazoles 5 [ 40 ], benzimidazoles 6 [ 40 41 ], diazines 7 [ 42 43 ], or imidazolines 8 ( Scheme 1 ) [ 44 ]. We have also shown that a nucleophilic attack on the phosphorylated nitronate species 2 can be carried out with the participation of N -acylhydrazides or thiosemicarbazides to afford the 1,3,4-oxadiazoles 9 [ 45 ] and the 1,3,4-thiadiazoles 10 [ 46 ], respectively ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] The utilization of nucleophilic amines was also demonstrated. [20][21][22][23][24] Mechanistically, the latter process is related to the classical Nef reaction, [25][26][27] employing aniline [20][21][22][23] or hydrazine 24 species 8 instead of water. It was proposed, that this reaction initially provides imidinium ion 9, that can be further employed as a convenient building block for the synthesis of heterocyclic Scheme 1 Formation of imidazolines.…”
Section: Resultsmentioning
confidence: 99%
“…compounds: benzoxazoles 10, benzimidazoles 11, diazines 12-13, [20][21][22][23] and oxadiazoles 14 (ref. 24) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Related processes, featuring nucleophilic secondary nucleophilic attack with nitrogen atom to form pyrimidine ring was also reported (Aksenov et al, 2016).…”
Section: Introductionmentioning
confidence: 90%